KEPEMIMPINAN NASIONALIS PERUSAHAAN SEBAGAI MEDIASI PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PERUSAHAAN UMUM DAN JASA DI KOTA BANDUNG - Kuswara, Galuh (JURNAL KEBANGSAAN RI, 2025)
Abstract: This study aims to analyze the effect of the work environment on employee job satisfaction, with nationalist leadership as a mediating variable in companies operating in the general trade and service sectors in Bandung City. The research background stems from the high employee turnover rate, which indicates low job satisfaction, despite companies providing physical facilities and work flexibility. This study uses a quantitative approach with Structural Equation Modeling (SEM) through AMOS 24.0 software. Data were collected from 200 employee respondents working at four companies using a digital questionnaire. The results show that the work environment has a positive and significant effect on employee job satisfaction, although the strength of this effect is not very strong. Furthermore, the work environment also has a moderately strong influence on nationalist leadership, and nationalist leadership has a significant and strong effect on job satisfaction. Nationalist leadership also serves as a significant mediating variable that strengthens the influence of the work environment on employee job satisfaction. These findings highlight the critical role of leaders in embedding national values within organizations as a strategic effort to increase employee loyalty and retention. This study offers a conceptual contribution to developing a value-based leadership style rooted in nationalism within modern human resource management practices. Keywords: Work environment, nationalist leadership, job satisfaction, turnover